Living Plant‐Hybrid Generators for Multidirectional Wind Energy Conversion. Issue 7 (12th May 2020) - Meder, Fabian; Thielen, Marc; Mondini, Alessio; Speck, Thomas; Mazzolai, Barbara
Abstract : The largest existing biological interface, the surface of living plants, as it stands is capable of converting mechanical energy into electricity based on a combination of contact electrification and electrostatic induction on the plant surface and its inner tissue. Herein, the first design strategies are reported for living plant‐based wind energy harvesting systems that use this effect and that are capable of harvesting simultaneously from multiple leaves of a single plant to upscale the energy output. This is the first study under outdoor‐relevant conditions in a controlled test environment that relates plant‐based energy conversion to wind speed and wind direction as well as parameters such as the environmental humidity. Increasing the wind speed not only leads to higher power but also low winds of 2 m s −1 and less can be converted into storable electricity. The plant‐hybrid generators are moreover capable of converting wind from multiple directions by exploiting the naturally multiplex leaf orientations and the plants can directly power light‐emitting diodes (LEDs) and a digital thermometer. The results draw attention to the opportunity to obtain living plant‐hybrid generators, e.g., for applications in constituting environmental sensor networks. Abstract : Green, carbon‐neutral energy obtained in a resource‐saving manner is crucial on large and small scales. Herein, the tissue structure of living plant leaves is exploited to transduce wind energy into electricity. A few leaves of a tree are sufficient to power light‐emitting diodes (LEDs) and sensors, and the results suggest essential design strategies for the first whole‐plant‐hybrid wind generators.